Occupational Safety and Health Facilities and Its Impact on Project Success: A Case Study of Narayangarh- Butwal (N-B) Road Project - Sanjel, Govinda (Journal of UTEC Engineering Management, 2023)
DOI: https://doi.org/10.36344/utecem.2023.v01i01.007The study was conducted in N-B road improvement project funded by Asian Development Bank (ADB) and implemented through International Competitive Bidding (ICB) . The research aims to focus on status of safety and health risk level of workers, assess the safety and health facilities provided to workers in selected road construction project.The primary data were collected through questionnaire and field observation whereas secondary data were collected through project contract documents and literature study. Basically, percentage- based data were generated and Relative Importance Index (RII), Spearman’s Rank Correlation Coefficient was calculated to analyze and interpret the data.As per the consultant, contractor and labor respondent’s response safe drinking water, first-aid/ medical facilities and provision of toilets were the top three ranked health facilities. Similarly, according to respondent safety signs and barriers, safety helmet and safety boots were the top three ranked safety provisions with RII of 98.25%, 96.87% and 96.22% respectively, showing that there is urgent need for upgrading or establishing these requirements at construction site. And, hazard identification, health facilities and safety provisions were ranked as first, second and third high impact factors for project success with RII of 94.07%, 91.85% and 84.44% respectively.Here it was found and concluded that the client and contractor are lacking to provide adequate safety and health facilities to the construction workers at workplace as per ILO provisions and Labor act 2017.